Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/10715760902736275
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondria targeted antioxidant MitoQ protects against fluoroquinolone-induced oxidative stress and mitochondrial membrane damage in human Achilles tendon cells

Abstract: Tendinitis and tendon rupture during treatment with fluoroquinolone antibiotics is thought to be mediated via oxidative stress. This study investigated whether ciprofloxacin and moxifloxacin cause oxidative stress and mitochondrial damage in cultured normal human Achilles' tendon cells and whether an antioxidant targeted to mitochondria (MitoQ) would protect against such damage better than a non-mitochondria targeted antioxidant. Human tendon cells from normal Achilles' tendons were exposed to 0-0.3 mM antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 31 publications
3
47
0
1
Order By: Relevance
“…Collins hopes to explore mitochondrial damage by antibiotics in other animal models. He and Murphy have also found, in lab studies 4,9 , that giving antioxidants alongside fluoroquinolones seems to mitigate the effects on mitochondria. Murphy is interested in trials to avoid mitochondrial toxicity in drugs; he owns shares in a company that aims to set some up.…”
Section: Lack Of Supportmentioning
confidence: 99%
“…Collins hopes to explore mitochondrial damage by antibiotics in other animal models. He and Murphy have also found, in lab studies 4,9 , that giving antioxidants alongside fluoroquinolones seems to mitigate the effects on mitochondria. Murphy is interested in trials to avoid mitochondrial toxicity in drugs; he owns shares in a company that aims to set some up.…”
Section: Lack Of Supportmentioning
confidence: 99%
“…Mitochondrial ROS production is a redox signal, mod- (Monboisse et al 1984;Bernard-Beaubois et al 1998;Shakibaei et al 2000;Reed 2000;Yuan et al 2003;Pouzaud et al 2004a;Sendzik et al 2005;Alberts et al 2008b;Lowes et al 2009;Murphy 2009;Aristilde et al 2010;Kaminski et al 2010).…”
Section: Test Agent Ultrastructural Changes Referenceunclassified
“…Concomitant use of antioxidants, such as N-acetylcysteine (Simonin et al 2000), anethole dithiolethione (Pouzaud et al 2004b), and MitoQ (Lowes et al 2009), was reported to attenuate toxic effects of FQs on tendon cells. Cotreatment with platelet rich plasma was proposed as a novel strategy to restore the reduced tenocyte viability and promote healing following FQ exposure (Zargar et al 2011).…”
Section: Test Agent Ultrastructural Changes Referencementioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in vivo studies demonstrate an enhanced efficiency and an improved cellular internalization of antioxidants when coupled to chitosan derivatives (26). Finally, antioxidants targeted specifically to the mitochondria have attenuated cell injury in oxidative stress-induced disease models (71,112).…”
Section: Antioxidants As Therapy For Bpdmentioning
confidence: 99%